Asuhan Kebidanan Pada Bayi Baru Lahir Di PMB Nurhayati Wilayah Kerja Puskesmas Air Tiris Tahun 2022 - Wahyuni, Indah Sari; Syahda, Syukrianti (Evidence Midwifery Journal, 2023)
The first few days of a newborn's life are very important, essential neonatal care should be provided at birth. There are many adjustments that babies go through as they transition from life in the womb to life outside the womb, including general awareness, early assessment, prevention of heat loss, cutting and care of the umbilical cord, early initiation of breastfeeding (IMD), prevention of bleeding, prevention of eye infections. , immunization, identification, history taking, and physical examination. The purpose of the case study is to find out and provide midwifery care for newborns at PMB Nurhayati, Air Tiris Health Center Work Area in 2022. The type of case study report uses the descriptive method, namely a research conducted to describe or describe a phenomenon that occurs. The results of the study showed that the subjective data of the mother said that this was the fourth child and had never miscarried, the objective data was that the general condition was good, the baby cried strongly, muscle tone was active, the skin was reddish. The assessment that can be enforced is that the baby, Mrs. E, a term neonate, is in good condition. The management provided was by keeping the baby warm, clearing the airway by sucking mucus, cutting the umbilical cord using umbilical cord clamps, doing Early Initiation of Breastfeeding, giving 1% oxytetracycline eye ointment, giving 1 mg vitamin K, giving HB0 vaccine, bathing the baby. At the 12-day visit, the umbilical cord had fallen off, general condition was good, muscle tone was active, weight was 3100 grams, skin color was reddish, and breastfeeding was strong. Provide motivation to give exclusive breastfeeding, keep the baby warm, remind the danger signs of newborns